Impact of Nickel Mining on River Pollution in North Konawe - Aliyyah Nisrina Taufik; Femy Febrianti Masaid; Nuryanti (Journal of Health Science and Pharmacy, 2025)
Background: Indonesia, as the country with the largest nickel reserves in the world, possesses vast natural resource potential. Southeast Sulawesi, particularly North Konawe Regency, has emerged as one of the central hubs of the national nickel mining industry. While this sector contributes positively to economic development, such as increasing production and creating employment opportunities, it also poses serious environmental threats most notably water pollution due to industrial waste. These risks highlight the critical importance of preparing Environmental Impact Assessment documents as a mitigation strategy to minimize negative environmental consequences. Objective: This study aims to analyze the impact of river pollution resulting from nickel mining activities in North Konawe Regency. Methods: This research employed a mixed-method approach, combining descriptive quantitative and qualitative analyses. The study primarily utilized secondary data sources, including statistical reports from the Central Bureau of Statistics, scientific journals, and electronic media. No primary data collection through interviews or direct observation was conducted. Results: Findings indicate that nickel production in North Konawe Regency exceeded 22 million tonnes in 2020. However, mining activities have resulted in serious environmental degradation, particularly affecting water bodies in approximately 128 villages. The discharge of industrial waste containing heavy metals has significantly compromised water quality and poses adverse health effects to surrounding communities. These outcomes underscore the urgent need for sustainable mining management practices to reduce environmental and public health risks. Conclusion: Nickel mining in North Konawe Regency has brought positive economic impacts, such as increased production and employment opportunities. However, it has also led to river pollution due to industrial waste containing heavy metals, which affects water quality and public health. Therefore, proper environmental management and the preparation of a comprehensive Environmental Impact Assessment are essential to minimize negative impacts and support the sustainability of mining activities. Keywords: River Pollution, Nickel Mining, North Konawe, Environmental Impact Assessment